Republic of Turkey : Sustainable Urban Water Supply and Sanitation - World Bank (World Bank, Washington, DC, 2017)
The main objective of this report is to identify and analyze the main issues faced by the WSS services in Turkey and to initiate a dialog with authorities on opportunitiesto enhance the quality, sustainability (technical and financial), and affordability of service provision as Turkey works to reach compliance with the European Union (EU) Drinking Water Directive (DWD) andthe Urban Wastewater Directive (UWWD) and with WSS related aspects of the EU Water Framework Directive (WFD). This objective is also very consistent with Turkey’s focus on reaching the recently established Sustainable Development Goals. The report identifies questions which were discussed ata high level workshop and related inputs subsequently received. Collecting and organizing the data necessary to perform in-depth analysis has provena challenge that could not be overcome in the timeframe of this study. The report therefore reliessolely on publicly available data and studies and on information collected through meetings withTurkish counterparts and EU colleagues and disseminated or validated at the workshop. This report is designed and written for high-level officials and authorities in central and localgovernments. Chapter one, which presents the sector’s main objectives, institutional arrangements,and regulatory framework, is kept short, as these are well-known to the target audience of thisreport.Chapter two presents an overview of the technical and financial status of the WSS.Chapter three compares the requirements of the EU Drinking Water and Urban Wastewater Directiveswith Turkish regulations and presents a short overview of the current compliance levels. Chapter four estimates the cost of reaching compliance with regulations related to wastewatercollection and treatment and service provisions in three scenarios: (i) under EU Urban Wastewater Directive requirements; (ii) under Turkish standards for nutrient removal in sensitive areas; and(iii) under Turkish standards of scenario 2, plus compulsory nitrogen removal treatment forcities of more than 50,000 people. It estimates the costs and operation and maintenance (O&M)requirements of existing infrastructure (per available data), incremental costs needed to complywith the regulations in each scenario, and where data is available, the related impact on O&Mand tariffs for utilities.Chapter five proposes questions worthy of further analysis which were discussed at a high-level workshop.